Recall and Unemployment - Fujita, Shigeru; Moscarini, Giuseppe (American Economic Review, 2017)
We document in the Survey of Income and Program Participation covering the period 1990–2013 that a surprisingly large share of workers return to their previous employer after a jobless spell, and experience very different unemployment and employment outcomes than job switchers. The probability of recall is much less procyclical and volatile than the probability of finding a new employer. We add to a quantitative, and otherwise canonical, search-and-matching model of the labor market a recall option, which can be activated freely following aggregate and job-specific productivity shocks. Recall and search effort significantly amplify the cyclical volatility of new job-finding and separation probabilities. (JEL E24, E32, J63, J64)